Ambient Humidity‐Induced Phase Separation for Fiber Morphology Engineering toward Piezoelectric Self‐Powered Sensing (Small 17/2022). Issue 17 (27th April 2022) - Lee, Sooun; Kim, Dabin; Lee, Sangryun; Kim, Yong‐Il; Kum, Sihyeon; Kim, Sang‐Woo; Kim, Yunseok; Ryu, Seunghwa; Kim, Miso
Abstract : Porous Piezoelectric Fibers In article number 2105811, Miso Kim and co‐workers establish a distinctive design approach to enhance piezoelectric performance via structural morphology tailoring in piezoelectric polymer fibers. Providing water molecules under ambient humidity conditions during electrospinning is the most crucial consideration in this study.